Navigating VUCA: Strategic Decision-Making in Iraqi Startups from a Dynamic Capabilities Perspective - Nazar Attyah Al-Rikabi , Kadhim (South Asian Journal of Social Sciences and Humanities, 2025)
Iraq’s fragile and resource-constrained entrepreneurial ecosystem exposes startups to persistent  environmental turbulence that challenges conventional decision-making structures. Drawing  on the theory of dynamic capability, this study examines how the four dimensions of the VUCA  environment—volatility, uncertainty, complexity, and ambiguity—shape the strategic decision making process in Iraqi startups. A quantitative cross-sectional research design was employed,  and survey data were collected from 200 founders and senior managers using validated five point Likert-type scales. Partial least squares structural equation modeling (PLS-SEM) was  applied to assess the measurement and structural models. The results indicate that all four  VUCA dimensions exert a positive and significant effect on the effectiveness of the strategic  decision-making process. Rather than treating VUCA conditions solely as constraints, Iraqi  startups appear to leverage them as catalysts for agility, experimentation, and learning-oriented  decision behavior. These findings extend dynamic capabilities theory to an emerging, post conflict context by suggesting that relational and intuitive forms of competence—such as  improvisation, experiential learning, and trust-based collaboration—can partially substitute for  formal structures and analytical routines. Practically, the study offers insights for entrepreneurs,  incubators, and policymakers on how to strengthen startups’ strategic responsiveness through  flexible planning, continuous environmental sensing, and dynamic learning mechanisms.
Keywords: Strategic decision-making; VUCA; dynamic capabilities; startups; Iraq